Ouabain potentiates the antimicrobial activity of aminoglycosides against Staphylococcus aureus - Neelam Kumari; Snehlata Singh; Vandana Kumari; Siddhartha Kumar; Vinay Kumar; Antresh Kumar (BMC, 2019)
Abstract Background Staphylococcus aureus is a notorious pathogen which often causes nosocomial and community attained infections. These infections steadily increased after evolving the resistance due to indecorous practice of antibiotics and now become a serious health issue. Ouabain is a Na+/K+-ATPase inhibitor that leads to increase the heart contraction in patients with congestive heart failure. Methods In the present study, in vitro antimicrobial effect of ouabain together with aminoglycosides was determined against clinical and non-clinical S. aureus strains. Using checkerboard, Gentamycin uptake and biofilm assays, we analysed he interactions of ouabain with aminoglycosides. Results Ouabain induced the staphylocidal potency of aminoglycosides by remarkably reducing the MIC of gentamycin (GEN) by 16 (0.25 μg/mL), 8 folds (0.5 μg/mL) amikacin (AMK); and 16 folds (1.0 μg/mL) with kanamycin (KAN), compared to their individual doses. OBN severely reduced cell viability within 60 min with GEN (1 μg/mL), KAN (2 μg/mL) and 90 min with AMK (1 μg/mL). This bactericidal effect was enhanced due to GEN uptake potentiated by 66% which led to increase the cell permeability as revealed by leakage of bacterial ATP and nitrocefin assay. The biofilm adherence disrupted by 80 and 50% at 5 mg/mL and 1.5 mg/mL OBN and 50 and 90% biofilm formation was inhibited at 5 mg/mL (MBIC50) and 10 mg/mL (MBIC90), respectively. Moreover, OBN with GEN further induced biofilm inhibition by 67 ± 5% at pH 7.0. Conclusions Taken together, we established that OBN synergizes the antimicrobial activity of aminoglycosides that induces cell killing due to intracellular accumulation of GEN by disturbing cell homeostasis. It may be proven an effective approach for the treatment of staphylococcal infections.